The economic and environmental effects of an EU ban on illegal logging imports: Insights from a CGE assessment - Francesco Bosello; Ramiro Parrado; Renato Rosa (Fondazione Eni Enrico Mattei (FEEM), 2010)
Illegal logging is widely recognized as a major economic problem and one of the causes of environmental degradation. Increasing awareness of its negative effects has fostered a wide range of proposals to combat it by major international conservation groups and political organizations. Following the 2008 US legislation which prohibits the import of illegally harvested wood and wood products, the European Union (EU) is now discussing a legislation proposal which would ban illegal timber from the EU market. In this study we use the ICES computable general equilibrium model to estimate the reallocation of global demand and timber imports following the pending EU legislation. With this exercise our final objective is to assess the economic impacts and measure the potential emission reduction resulting from the introduction of this type of policy. Results show that while the EU ban does not seem particularly effective in reducing illegal logging activities, its main effect will be the removal of illegal logs from the international markets. In addition, the unilateral EU ban on illegal logs increases secondary wood production in illegal logging countries as their exports become relatively more competitive. Through this mechanism, part of the banned, illegal timber will re-enter the international trade flows, but it will be 'hidden' as processed wood. This effect is, however, limited. Finally, given the limited effect on overall economic activity, effects on GHG emissions are also limited. Direct carbon emissions from logging activities can decrease from 2.5 to 0.6 million tons per year.
Keywords: D58; Q23; Q56; R13; 330; Forestry; Illegal Logging; International Trade; Economy and Environment; Computable General Equilibrium Models